How to discuss about do-not-resuscitate in the intensive care unit? - Teixeira, Cassiano (Rev Bras Ter Intensiva, 2019)
The improvement in cardiopulmonary resuscitation quality has reduced the mortality of individuals treated for cardiac arrest. However, survivors have a high risk of severe brain damage in cases of return of spontaneous circulation. Data suggest that cases of cardiac arrest in critically ill patients with non-shockable rhythms have only a 6% chance of returning of spontaneous circulation, and of these, only one-third recover their autonomy. Should we, therefore, opt for a procedure in which the chance of survival is minimal and the risk of hospital death or severe and definitive brain damage is approximately 70%? Is it worth discussing patient resuscitation in cases of cardiac arrest? Would this discussion bring any benefit to the patients and their family members? Advanced discussions on do-not-resuscitate are based on the ethical principle of respect for patient autonomy, as the wishes of family members and physicians often do not match those of patients. In addition to the issue of autonomy, advanced discussions can help the medical and care team anticipate future problems and, thus, better plan patient care. Our opinion is that discussions regarding the resuscitation of critically ill patients should be performed for all patients within the first 24 to 48 hours after admission to the intensive care unit.